2004
DOI: 10.1111/j.1559-1816.2004.tb01991.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of African American Skin Color on Hiring Preferences1

Abstract: The role of African American skin color in hiring decisions was investigated in a 2 × 2 × 2 (Participant Sex × Applicant Sex × Applicant Skin Color) design. College‐age participants (N= 107) were presented with stimuli and asked to make 8 employment‐related decisions. An interaction of applicant skin color and participant sex and a skin‐color main effect were predicted. Fair‐skinned applicants were expected to receive better ratings from men, while dark‐skinned applicants were expected to receive better rating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…Existing studies have exclusively focused on Black men as targets, and to date no Afrocentric features research has used Black women as targets. Gender differences have been reported in skin tone research (Coard, Breland, & Raskin, 2001;Hill, 2002;Ross, 1997;Thompson & Keith, 2001;Wade & Bielitz, 2005;Wade et al, 2004), thus the effects of facial features also may be different for Black men and women. Additionally, as already stated above, social dominance theory predicts target gender differences in racial bias.…”
Section: Limitations and Future Directionsmentioning
confidence: 94%
See 2 more Smart Citations
“…Existing studies have exclusively focused on Black men as targets, and to date no Afrocentric features research has used Black women as targets. Gender differences have been reported in skin tone research (Coard, Breland, & Raskin, 2001;Hill, 2002;Ross, 1997;Thompson & Keith, 2001;Wade & Bielitz, 2005;Wade et al, 2004), thus the effects of facial features also may be different for Black men and women. Additionally, as already stated above, social dominance theory predicts target gender differences in racial bias.…”
Section: Limitations and Future Directionsmentioning
confidence: 94%
“…Research of skin tone has consistently shown that darker-skinned Blacks are perceived, evaluated, and treated more negatively than lighter-skinned Blacks by both Whites and Blacks (Anderson & Cromwell, 1977;Averhart & Bigler, 1997;Dixon & Maddox, 2005;Hall, 1992Hall, , 2003Hall, , 2005Maddox & Chase, 2004;Maddox & Gray, 2002;Wade, Romano, & Blue, 2004). Research of Afrocentric features has also shown that facial features, such as fuller lips, wider nose, and coarse hair, in addition to darker skin, negatively influence Whites' reactions to Blacks (Blair, 2006;Blair, Chapleau, & Judd, 2005;Blair, Judd, & Fallman, 2004;Blair, Judd, Sadler, & Jenkins, 2002;Eberhardt, Davies, Purdie-Vaughns, & Johnson, 2006;Eberhardt, Goff, Purdie, & Davies, 2004;Livingston & Brewer, 2002).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Darker-skinned blacks, in short, were more ''deathworthy'' and less deserving of emergency assistance. Though arriving at more complex findings, audit studies of housing and experimental studies of hiring have also documented differential treatment by skin tone (Yinger 1995;Wade et al 2004); in the latter study, participants preferred light-skinned applicants to blacks with a darker appearance in an exercise in which they were asked to hire for an engineering firm. And perceptions of blacks themselves seem to reflect differential treatment by color, as darker-skinned blacks reported more discrimination than light-skinned blacks (Klonoff and Landrine 2000).…”
Section: Why Color and Phenotype?mentioning
confidence: 98%
“…In the United States and many other places, darker skin tone is linked to lower social status even when background characteristics are kept constant (e.g., Hunter, 2007;Smith-McLallen, Johnson, Dovidio, & Pearson, 2006;Uhlmann et al, 2002). Among African Americans, darker skin tone is related to lower educational attainment, occupational prestige, and family and personal income compared to lighter skin tone (e.g., Keith & Herring, 1991;Wade, Romano, & Blue, 2004). Research shows that both Whites and African Americans still associate different stereotypes with African Americans based on skin tone (Dixon & Maddox, 2005;Maddox & Gray, 2002).…”
Section: Skin Tone and Skin Tone Biasmentioning
confidence: 99%